2017
DOI: 10.18186/journal-of-thermal-engineering.330184
|View full text |Cite
|
Sign up to set email alerts
|

PERFORMANCE MAP MEASUREMENT, ZERO-DIMENSIONAL MODELLING & VIBRATION ANALYSIS OF A SINGLE CYLINDER DIESEL ENGINE

Abstract: Single Cylinder Diesel Engines are simple and very economical in manufacturing. Their multipurpose usability and the capability to deliver the maximum power possible within a given envelope makes them very demanding engines in the market. Simulation tools are widely used nowadays to minimize the energy and time needed for a real engine design and development. Zero-dimensional models are very suitable and reliable to observe the engine operation under different conditions. Contrary to the previous studies, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results of study show that the distribution magnitude of internal heat for body nose temperature is directly proportional with attack angle and Mach number. Kaan et al [9][10][11][12] performed measurements for real-time air quality of emissions for three months in Ambarli, Marport Terminal. In their research, critical times of all the emissions are specified between the measured dates using CFD modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The results of study show that the distribution magnitude of internal heat for body nose temperature is directly proportional with attack angle and Mach number. Kaan et al [9][10][11][12] performed measurements for real-time air quality of emissions for three months in Ambarli, Marport Terminal. In their research, critical times of all the emissions are specified between the measured dates using CFD modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Monolith was considered as porous medium and the values of parameters are determined at three sections. Validation of design was carried out by flow and pressure drop analysis [25]. Results showed that sudden expansion of diffuser at inlet resulted in recirculation zone which would lead to Journal of Thermal Engineering, Review Article, Vol.…”
Section: Cfd Analysis Of Doc Filtermentioning
confidence: 99%
“…A study comparing the experimental results with numerical modelling results was performed before in [18]. But as per our knowledge, no previous study has been done comprising of a detailed model especially implementing VCR directly in the numerical model and comparing the performance parameters in terms of engine maps.…”
Section: Introductionmentioning
confidence: 99%